Integrating exome sequencing into a diagnostic pathway for epileptic encephalopathy: Evidence of clinical utility and cost effectiveness. Issue 2 (4th January 2018) - Palmer, Elizabeth E.; Schofield, Deborah; Shrestha, Rupendra; Kandula, Tejaswi; Macintosh, Rebecca; Lawson, John A.; Andrews, Ian; Sampaio, Hugo; Johnson, Alexandra M.; Farrar, Michelle A.; Cardamone, Michael; Mowat, David; et al.
Abstract: Background: Epileptic encephalopathies are a devastating group of neurological conditions in which etiological diagnosis can alter management and clinical outcome. Exome sequencing and gene panel testing can improve diagnostic yield but there is no cost‐effectiveness analysis of their use or consensus on how to best integrate these tests into clinical diagnostic pathways. Methods: We conducted a retrospective cost‐effectiveness study comparing trio exome sequencing with a standard diagnostic approach, for a well‐phenotyped cohort of 32 patients with epileptic encephalopathy, who remained undiagnosed after "first‐tier" testing. Sensitivity analysis was included with a range of commercial exome and multigene panels. Results: The diagnostic yield was higher for the exome sequencing (16/32; 50%) than the standard arm (2/32; 6.2%). The trio exome sequencing pathway was cost‐effective compared to the standard diagnostic pathway with a cost saving of AU$5, 236 (95% confidence intervals $2, 482; $9, 784) per additional diagnosis; the standard pathway cost approximately 10 times more per diagnosis. Sensitivity analysis demonstrated that the majority of commercial exome sequencing and multigene panels studied were also cost‐effective. The clinical utility of all diagnoses was reported. Conclusion: Our study supports the integration of exome sequencing and gene panel testing into the diagnostic pathway for epileptic encephalopathy, both in terms of cost effectiveness and clinical utility. We propose a diagnostic pathway that integrates initial rapid screening for treatable causes and comprehensive genomic screening. This study has important implications for health policy and public funding for epileptic encephalopathy and other neurological conditions. Abstract : This study uniquely compares the diagnostic yield, cost effectiveness, and clinical utility of the exome diagnostic model over the standard diagnostic model for patients with epileptic encephalopathy, who remain undiagnosed after first‐tier assessment. Our findings strongly support the exome diagnostic model, which resulted in a cost saving of AU$5, 236 per additional diagnosis: approximately 10 times less expensive per diagnosis than the standard diagnostic model. We thus propose an optimal approach for the investigation of epileptic encephalopathy that benefits patients and their families by reducing the length and invasiveness of the "diagnostic odyssey" and provides a cost saving for the health budget.